2016
DOI: 10.1002/anie.201511433
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Functionalized Pyrrolidines by the Diverted N−H Insertion Reaction of Metallocarbenes with β‐Aminoketone Derivatives

Abstract: A highly stereoselective route to functionalized pyrrolidines by the metal‐catalyzed diverted N−H insertion of a range of diazocarbonyl compounds with β‐aminoketone derivatives is described. A number of catalysts (rhodium(II) carboxylate dimers, copper(I) triflate, and an iron(III) porphyrin) are shown to promote the process under mild conditions to give a wide range of highly substituted proline derivatives. The reaction starts as a metallocarbene N−H insertion but is diverted by an intermolecular aldol react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 45 publications
(20 reference statements)
0
27
0
1
Order By: Relevance
“…3141 Furthermore, several reactive intermediates, such as carbonyl ylides, oxonium ylides, azomethine ylides, and nitrones, can be generated from diazo compounds in the presence of transition metal catalysts and then undergo intermolecular cycloaddition or intramolecular ring closure. 16,32,34,39,4253 Additionally, the successful combination of metal carbene chemistry and other catalytic strategies ( e.g. , C–H activation, 45,5462 C–C cleavage, 6366 and gold catalysis 17,46,6770 ) is fully illustrated by recent advances in cycloaddition reactions of diazo compounds.…”
Section: Introductionmentioning
confidence: 99%
“…3141 Furthermore, several reactive intermediates, such as carbonyl ylides, oxonium ylides, azomethine ylides, and nitrones, can be generated from diazo compounds in the presence of transition metal catalysts and then undergo intermolecular cycloaddition or intramolecular ring closure. 16,32,34,39,4253 Additionally, the successful combination of metal carbene chemistry and other catalytic strategies ( e.g. , C–H activation, 45,5462 C–C cleavage, 6366 and gold catalysis 17,46,6770 ) is fully illustrated by recent advances in cycloaddition reactions of diazo compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a diastereoselective approach to the synthesis of indolines via intramolecular trapping of ammonium ylides with ketones [11] and double bonds [12] was developed. C. J. Moody and co-workers elaborated an efficient way for the synthesis of pyrrolidines by trapping of ammonium ylides with ketones [13], whereas J. Sun and colleagues showed that similar reactions can be extended to compounds with triple bonds and allene fragments [14].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Herein, the intermolecular reactivity of N-aryl g-lactams 1 with a-diazodicarbonyl compounds 2 is reported (Scheme 1, bottom). [6] In fact, amide groups are transformed into amines with adjacent acetyl and 2-oxoethanoate chains in one step. [6] In fact, amide groups are transformed into amines with adjacent acetyl and 2-oxoethanoate chains in one step.…”
mentioning
confidence: 99%
“…[5] Highly functionalized pyrrolidines 3 with a-pseudoquaternary centers are obtained in good yields (up to 83 %). [6] In fact, amide groups are transformed into amines with adjacent acetyl and 2-oxoethanoate chains in one step. This transformation, which involves acyl (or phosphoryl) group migration, proceeds with very high regioselectivity and is specifically catalyzed by copper salts (10 mol %).…”
mentioning
confidence: 99%